Effects of clown doctors on child and caregiver anxiety at the entrance to the surgery care unit and separation from caregivers - Arriaga, P.; Pacheco, C. (International Journal of Emotional Education, 2016)
This study investigated the effects of hospital Clown Doctors intervention on child and caregiver preoperative anxiety at the entrance to the surgery care unit and separation from caregivers. A total of 88 children (aged 4-12 years) were assigned to one of the following two groups: Clown Doctors intervention or control group (standard care). Independent observational records using the modified Yale Preoperative Anxiety Scale instrument assessed children’s anxiety, while the State-Trait Anxiety Inventory measured caregiver’s state anxiety. In addition, caregivers assessed the children’s functional health problems by completing the Functional Status Questionnaire. Although no effects of Clown Doctors were found on children’s anxiety, results showed that both low functional health problems and Clown Doctors intervention were significant predictors of lower caregiver anxiety. Caregivers also reported being very satisfied with their intervention. Overall, this study demonstrated the positive role of Clown Doctors for caregivers at a specific pediatric hospital setting.